2014
DOI: 10.1103/physrevc.90.044901
|View full text |Cite
|
Sign up to set email alerts
|

Heavy-flavor in-medium momentum evolution: Langevin versus Boltzmann approach

Abstract: The propagation of heavy quarks in the quark-gluon plasma (QGP) has been often treated within the framework of the Langevin equation (LV), i.e. assuming the momentum transfer is small or the scatterings are sufficiently forward peaked, small screening mass mD. We address a direct comparison between the Langevin dynamics and the Boltzmann collisional integral (BM) when a bulk medium is in equilibrium at fixed temperature. We show that unless the cross section is quite forward peaked (mD ∼ = T ) or the mass to t… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
114
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 119 publications
(117 citation statements)
references
References 62 publications
3
114
0
Order By: Relevance
“…For bottom quarks the Fokker Planck and the Boltzmann approach yield almost identical results. For the charm quarks differences between both approaches have been reported [135] what should be investigated in detail in near future.…”
Section: Model Testsmentioning
confidence: 99%
See 1 more Smart Citation
“…For bottom quarks the Fokker Planck and the Boltzmann approach yield almost identical results. For the charm quarks differences between both approaches have been reported [135] what should be investigated in detail in near future.…”
Section: Model Testsmentioning
confidence: 99%
“…In the last years, several groups have advanced approaches, which study the interaction of heavy quarks in an expanding QGP [61,[89][90][91][130][131][132][133][134][135][136][137][138][139][140][141][142][143][144]. These approaches are either based on a Fokker-Planck equation or on the use of the full Boltzmann collision kernel to describe the collisions of heavy quarks with the partons of the QGP.…”
Section: Model Testsmentioning
confidence: 99%
“…The comparison between LV and BM approach has been thoroughly studied in these references [15,16] where it is shown that for charm quark the results that one gets using the Fokker-Planck approach deviate significantly from those obtained using the Boltzmann approach and such a deviation significantly depends on the the values of the Debye screening mass, whereas for bottom quarks the FP is a very good approximation. We considered in references [15,16] three values of m D : 0.4 GeV, 0.83 GeV and 1.6 GeV. Here we have not considered a fixed value of the Debye screening mass but a value which depends on the temperature according to m D = gT .…”
Section: Introductionmentioning
confidence: 99%
“…The two key observables related to HQ that have been measured in experiments are the nuclear suppression factor R AA and the elliptic flow v 2 [3][4][5]. Several theoretical efforts have been made to study the R AA and the v 2 measured in experiments within the Fokker Planck (FP) approach [6-9, 11, 12] and the relativistic Boltzmann approach (BM) [13][14][15][16]. However all the approaches show some difficulties to describe both the nuclear modification factor and the elliptic flow simultaneously.…”
Section: Introductionmentioning
confidence: 99%
“…To address this, one requires to describe the dynamics of the HQs propagating through the QGP. Therefore, one can explore the physics of the HQ transport [4][5][6][7][8][9][10][11][12][13][14][15][16][17][18][19][20][21] in the QGP medium as follows.The non-equilibrated HQs can travel in the equilibrated QGP medium, and one has to deal the problem within the framework of Langevin dynamics [22]. This is to say that the HQs perform random motion in the equilibrated QGP.…”
Section: Introductionmentioning
confidence: 99%